2006
DOI: 10.1100/tsw.2006.48
|View full text |Cite
|
Sign up to set email alerts
|

The Riddle of Ball Lightning: A Review

Abstract: One of the most intriguing and enduring scientific challenges is to find an explanation for ball lightning, the shining fireballs that sometimes appear near lightning strokes. Although many theoretical ideas have been proposed and much experimental work has been performed, there is not yet an accepted explanation of their amazing properties. They are surprisingly stable, lasting up to 10 s, even minutes in some rare cases. By night, their appearance can be spectacular, but their brilliance is just similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…As it has been noted in the introduction a number of models for the ball lightning have been developed. Their description is given in (Kapitza 1955;Singer 1971;Bary 1980;Dijkhuis 1981;Bychkov et al 1993;Turner 1994;Lowke 1996;Stakhanov 1996;Sinkevich 1997;Stenhoff 1999;Fedosin and Kim 2001;Torchigin and Torchigin 2004;Furov 2005;Coleman 2006;Donoso et al 2006;Grigor'ev 2006;Kuz'min et al 2006;Nikitin 2006;Mitchell et al 2008;Ionita et al 2009;v. Wurden and Wurden 2011;Ofuruton et al 2011;Dvornikov 2012;Meessen 2012).…”
Section: Ball Lightning As An Electrical Domain Of Spherical Shapementioning
confidence: 99%
See 1 more Smart Citation
“…As it has been noted in the introduction a number of models for the ball lightning have been developed. Their description is given in (Kapitza 1955;Singer 1971;Bary 1980;Dijkhuis 1981;Bychkov et al 1993;Turner 1994;Lowke 1996;Stakhanov 1996;Sinkevich 1997;Stenhoff 1999;Fedosin and Kim 2001;Torchigin and Torchigin 2004;Furov 2005;Coleman 2006;Donoso et al 2006;Grigor'ev 2006;Kuz'min et al 2006;Nikitin 2006;Mitchell et al 2008;Ionita et al 2009;v. Wurden and Wurden 2011;Ofuruton et al 2011;Dvornikov 2012;Meessen 2012).…”
Section: Ball Lightning As An Electrical Domain Of Spherical Shapementioning
confidence: 99%
“…A number of models for ball lightning have been developed. Descriptions of the existing models are given in monographs (Singer 1971;Bary 1980;Stakhanov 1996;Stenhoff 1999;Grigor'ev 2006) and review papers (Sinkevich 1997;Donoso et al 2006;Nikitin 2006). The fact that the ball lightning is generated in an electrical discharge is a single general feature for majority of the models.…”
Section: Introductionmentioning
confidence: 99%
“…Any model of BL (electrostatic, electrochemical, charged aerosols and fractals, nuclear, plasma, etc. ; for reviews see Donoso et al, 2006;Oreshko, 2015) must predict all the reported characteristics of BL. Moreover, any experiment to generate BL must fully replicate its properties (for reviews see Bychkova et al, 2016;Stephan et al, 2016;Wu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ball lightning has been the subject of a great deal of interest (Donoso et al 2006), and although many mechanisms of production have been postulated (Turner 1998), a complete theory remains elusive (Stenhof 1999). Theories that have been put forward to explain ball lightning include antimatter (Ashby & Whitehead 1971), electromagnetic standing waves within a ball of plasma (Watson 1960), retinal after images (Argyle 1971; *sw.hughes@qut.edu.au Charman 1971), electromagnetic knots (Ranada & Trueba 1996), oxidation of nanoparticles (Abrahamson & Dinniss 2000), corona discharge generated by dissipating electrical ground currents (Lowke 1996), microwave interference (Ohtsuki & Ofuruton 1991), plasma surrounded by hydrated ions (Turner 1994), superconducting plasma vortices (Dijkhuis 1980), polymer composites (Bychkov & Bychkov 2002), light bubbles (Torchigin & Torchigin 2007) and even black holes of cosmic origin (Muir 2007).…”
Section: Introductionmentioning
confidence: 99%